A Study of Diatom Abundance Changes and Silicate Uptake Using an Enrichment Experiment - Darwich, Feirouz (Latakia University Journal -Biological Sciences Series, 2013)
This study describes the potency of natural groups of diatoms to consume the silicate concentrations from media, and the changes in the cell content of silicate under different Si:N ratios. Using unfiltered seawater, the experiments were carried out at two stations in the northern part of Lattakia coastal water during March, June, and October 2010 and January and August 2011. In general, diatoms were able to consume all the available silica in the cultivated media even after nitrate and phosphate depletion at the end of the experiment, unlike what happens in natural environments. Silicate is incorporated into diatom frustules, this leads to an increase in the cell content of silicate under high Si:N ratios.